In-situ growth of N@MoO2 microflowers on carbon cloth for high-performance anodes in microbial fuel cells. Issue 3 (June 2022) - Hu, Fangming; Qiu, Zhenghui; Zhang, Zhaoqi; Zheng, Jiyong; He, Lijun; Gao, Haiping; Lin, Cunguo
Abstract: Anode is a crucial component enabling microbial fuel cells (MFCs) to achieve efficient and durable power generation; however, the preparation of high-performance and up-scaling anodes via facile methods remains a practical challenge. In this study, a nitrogen-doped carbon cloth grafted with molybdenum dioxide microspheres (N @ MoO2 /CC) was fabricated using a facile two-step method: in situ polymerization and high-temperature carburization. N @ MoO2 /CC exhibited excellent bioelectricity harvesting capacity owing to its dual function of promoting bacterial colonization while enriching electroactive bacteria. The synergy of N-doping and MoO2 -grafting enabled the development of a biocompatible interface for bacterial adhesion, resulting in a high bacterial loading capacity. Furthermore, N-doping and MoO2 -grafting modifications facilitated the enrichment of Geobacter, thereby enhancing the electrocatalytic activity of the electrode. MFC equipped with N @ MoO2 /CC achieved a maximum power density of 3.01 ± 0.23 W·m −2, i.e., 1.43 times the power density achieved using a pristine carbon cloth (2.10 ± 0.04 W·m −2 ). Additionally, the physical and electrochemical characterizations confirmed that the as-prepared N @ MoO2 /CC exhibited excellent operational stability. In summary, N @ MoO2 /CC could significantly enhance bacterial colonization, enable electroactive bacteria to flourish, and boost charge transfer efficiency at the microbe–electrode interface, thus improving the electricity generation in MFCs. Graphical Abstract: ga1 Highlights: N-doped carbon cloth grafted with molybdenum dioxide microspheres (N @ MoO2 /CC) was as anode of microbial fuel cell. N @ MoO2 /CC was obtained using a facile two-step method: in-situ polymerization and carburization. N @ MoO2 /CC had good biocompatibility and promoted bacterial colonization. N-doping and MoO2 grafting modifications facilitated the enrichment of electroactive bacteria. N @ MoO2 /CC could boost the electron harvesting capacity of microbial fuel cells.